(untitled) (Swiss Medical Weekly, 2022)
AIMS OF THE STUDY: In Switzerland, COVID-19 vaccines have been approved for children aged 5–11 years only recently, whereas vaccination of adolescents aged 12 years and older was approved in early summer 2021. Although the disease burden in children and adolescents has been reasonably mild, they can transmit COVID-19 to others, thus vaccinating this age group may help to curb the COVID-19 pandemic. The main objective was to investigate the association between five psychological antecedents of vaccination hesitancy in COVID-19 immunised parents and their intention to have their child vaccinated against COVID-19. Further, we examined if parental vaccination history and conviction of the benefits of Swiss paediatric vaccination recommendations are associated with child vaccination intention, and where parents would like the vaccination performed. METHODS: A cross-sectional anonymous online survey in the COVID-19 vaccination centre Winterthur was conducted between 16 May and 30 September 2021. Individuals receiving COVID-19 vaccines in the vaccination centre were invited to participate. All individuals who participated in the survey after their first dose with children under 16 years were included in the analysis (n = 1318). Using multivariable logistic regression, the association between our main predictor variables, psychological antecedents (confidence, constraints, complacency, calculation, collective responsibility) measured by the validated 5C scale, and parents’ intention to have their child vaccinated against COVID-19 was analysed, adjusted for parental vaccination history, conviction of benefits of vaccination recommendations for children and adults, children’s age group, sociodemographic factors, and time-point of vaccine authorisation for 12–16-year-olds. RESULTS: 58.7% of the parents intended to vaccinate their child against COVID-19. Their preferred vaccination location for their child was the paediatrician or family doctor. Three psychological antecedents were associated with vaccination intention: confidence (adjusted odds ratio [AOR] 1.33, 95% confidence interval [CI] 1.00–1.76; borderline significant), calculation (AOR 0.68, 95% CI 0.58–0.81), and collective responsibility (AOR 1.93, 95% CI 1.47–2.52). Influenza vaccination (AOR 1.53, 95% CI 1.15–2.03) and conviction of the benefits of the Swiss vaccination recommendations for children and adolescents were independently associated with parental vaccination intention. CONCLUSIONS: Campaigns on COVID-19 vaccination for children may increase the intention of parents to have a child vaccinated when they address collective responsibility and calculation (weighing risks and benefits), independent of the conviction of the benefits of the vaccination recommendations, which was also a significant factor. The findings further show that parents of younger children favour their paediatrician or family doctor over vaccination centres as the vaccination setting for their child, an important finding for paediatric COVID-19 vaccination strategies.